Analisis Penerapan Indexing dan Query Optimization pada Database MySQL untuk Meningkatkan Performa Aplikasi Absensi Mahasiswa Universitas Pamulang - Naufal Skha Yusfa, Muhammad; Musyawwa, Ahyat; Bifal Pratama, Aldy (PT Jurnal Cendekia Indonesia, 2025)
At Pamulang University, student attendance is recorded through two mechanisms: the online My Unpam platform and traditional paper-based sheets. In practice, the offline method is still more commonly used due to unstable campus network connectivity, resulting in delays of 10–15 minutes at the beginning of each class. This study examines how the use of indexing and query optimization in MySQL can enhance the performance of a web-based attendance system, allowing the online method to operate more efficiently and reliably. The research framework includes a situational analysis involving lecturers and Information Systems students, followed by simulated testing using 30 dummy student records. Optimization techniques such as creating indexes on NIM and date fields and evaluating queries with EXPLAIN are applied within a PHP-based prototype. The outcomes include an improved PHP-MySQL attendance prototype and instructor guidelines to support system adoption. This work aims to reduce dependence on manual attendance practices and strengthen digital transformation initiatives in higher education by improving database responsiveness and overall system performance.